213k views
3 votes
Problem 2 What are the solutions to the quadratic equation 2 x + 6x - 6 = 0? -5.12, -0.87 -4.73,-1.27 -13.61, 7.61 -10.75 4.75 -6.87, 0.87

User Eustace
by
5.3k points

1 Answer

4 votes

To solve for the quadratic equation given, we shall use the quadratic equation formula as follows;


\begin{gathered} x^2+6x-6=0 \\ x=\frac{-b\pm\sqrt[]{b^2-4ac}}{2a} \\ \text{Where a=1, b=6, and c=-6} \\ x=\frac{-6\pm\sqrt[]{6^2-4(1)(-6)}}{2(1)} \\ x=\frac{-6\pm\sqrt[]{36+24}}{2} \\ x=\frac{-6\pm\sqrt[]{60}}{2} \\ x=(-6\pm7.75)/(2) \\ x=(-6+7.75)/(2),x=(-6-7.75)/(2) \\ x=0.875,x=-6.875 \end{gathered}

The answers are approximately x = 0.87, OR x = -6.87

User Pablo Lopez
by
4.5k points